THE CONCEPT OF WORK ETHIC IN ORDER TO IMPROVE THE QUALITY OF WORK IN ISLAMIC ECONOMIC PERSPECTIVE - Akhmad Hulaify; Syahrani Syahrani (AL-ULUM : Jurnal Ilmu Sosial dan Humaniora, 2018)
This research entitled the concept of work in improving the quality of work in perspective of Islamic economics. The orientation of ethic in the study of Islamic economics perspective is to discover work ethic of the essence of a work that expected to increase the quality of work. Based on the intention of this research, the author used sociology approach and normative approach. The aim of this research is to analyze how the study of wok ethics in Islamic economics perspective, it is expected that with those approach, this study can reveal the ethics values from Islamic law side. Beside of that, this study also discusses the result of research using qualitative descriptive analysis model. The analysis is meant to describe the meaning of work ethic not only in one economic point of view but from the perspective of Islamic Economics. Besides, the analysis is intended to get a new perspective to work ethics concept oriented to the essence of faith.       The conclusion of this research is manifestation of faith that implemented in the quality of work then work orientation will lack the sincere and good pleasure of Allah SWT.  Therefore, the orientation of work is not only because material but ridha Allah SWT. If it has become a spirit in work the meaning of falah in the concept of Islamic Economy is realized and fulfilled. Keywords:Ethis, Works, Quality, Islamic Economics.